Touched by Love: Spiritual Experience in Chinese Christian Conversion Narratives. Issue 1 (May 2022) - Scorgie, Glen G.; Scorgie, Kate; Chow, Alexander; Hsieh, Nicholas
Christianity has become the religion of choice for a growing number of diasporic Chinese. This qualitative study examines the conversion narratives of first-generation Chinese converts to evangelical Protestant Christianity, exploring in particular the spiritual experiences that encouraged or confirmed their resolve to become Christians. Utilizing the method of Interpretative Phenomenological Analysis (IPA), twenty English-speaking participants were interviewed, mostly immigrants to the United States or the United Kingdom from China, including Hong Kong, or from Taiwan. The converts to Christianity in this study were in search of an intellectually plausible faith, and an overarching framework of meaning, purpose, and fullness for their lives, and were motivated as well by longings for community and belonging. Participants reported being profoundly "touched"—inexplicably moved—by the love extended to them by other Chinese Christians, and being transformed in wide-ranging and durable ways as a result. In their view, such love was qualitatively different from, and superior to, the more transactional relational dynamics with which they had been familiar. They inferred that it was "otherworldly, " and necessarily emanated from a real and unconditionally benevolent divine source. The study thus illuminates the spiritual dynamics that persist in Chinese Christian conversions, even in a secular age.